2015
DOI: 10.4238/2015.march.30.26
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression profile of an ATP-binding cassette (ABC) transporter gene from the hemipteran insect Nilaparvata lugens

Abstract: ABSTRACT. The ATP-binding cassette (ABC) transporters belong to a large superfamily of proteins that have important physiological functions in all living organisms. In insects, ABC transporters have important functions in the transport of molecules, and are also involved in insecticide resistance, metabolism, and development. In this study, the Nilaparvata lugens Stal (Hemiptera: Delphacidae) ABCG (NlABCG) gene was identified and characterized. The complete mRNA sequence of NlABCG was 2608-bp long, with an ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…; Zha et al . ); however, it was found that their expression was not sufficiently stable. Conversely, RPS11 was found to be a stably expressed reference gene present at different developmental stages and in different body parts (Yuan et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…; Zha et al . ); however, it was found that their expression was not sufficiently stable. Conversely, RPS11 was found to be a stably expressed reference gene present at different developmental stages and in different body parts (Yuan et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…In some insects, P-gps and MRPs are expressed at higher levels in the midgut and Malpighian tubules than in other tissues (Leader and O'Donnell, 2005;Tian et al, 2013;Hull et al, 2014;Guo et al, 2015;Zha et al, 2015), which may result in greater inhibition of P-gp/MRP activity within the digestive system. In the present study, the CR strain treated with chlorpyrifos and verapamil had a two-fold decrease in toxicity compared to the SS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PxPgp1 is expressed throughout all developmental stages of P. xylostella, and the expression level increases continually throughout development (Tian et al, 2013). Likewise, HaABCC2 and NlABCG expressions increase rapidly with larval growth in Helicoverpa armigera and N. lugens, respectively (Yang, 2013;Zha et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The ATP-binding cassette (ABC) transporters are responsible for import and export of substrates across the membrane in an ATP dependent manner (Nuruzzaman et al 2014;Andolfo et al 2015). ABC family is one of the largest and oldest protein families discovered so far, and is found widely in archaea, bacteria and eukaryotes (Kim et al 2013;Andolfo et al 2015;Zha et al 2015). The typical ABC transporter contains both transmembrane domains (TMD) and ATP-binding domains, which are also called nucleotide-binding domains (NBD) (Zha et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…ABC family is one of the largest and oldest protein families discovered so far, and is found widely in archaea, bacteria and eukaryotes (Kim et al 2013;Andolfo et al 2015;Zha et al 2015). The typical ABC transporter contains both transmembrane domains (TMD) and ATP-binding domains, which are also called nucleotide-binding domains (NBD) (Zha et al 2015). The structures of TMDs are generally not conserved (Smart and Fleming 1996;Van and Tampe 2004;Rea 2007).…”
Section: Introductionmentioning
confidence: 99%